The effect of backpack load on intersegmental motions of the foot and plantar pressure in individuals with mild flatfoot - Min Gyu Kyung; Ppu Ri Bak; Jong Wook Lim; Dong‐Oh Lee; Gil Young Park; Dong Yeon Lee (Journal of Foot and Ankle Research, 2022)
Abstract Background The feet play an essential role in shock absorption, and foot posture is closely related to gait. The compensatory mechanism under heavy‐load conditions in individuals with mild flatfoot is poorly understood. In the authors' country, individuals with mild flatfoot are drafted as active‐duty soldiers and participate in military rucking wearing heavy backpacks. This study investigated the effect of backpack load on gait and foot plantar pressure and possible differences in participants with mild flatfoot. The average weight of the backpack during military rucking (approximately 20 kg), was simulated in this study. Methods This study prospectively enrolled 30 healthy young males, divided into a control group (CON, n = 15) and a mild low‐arched group (MLA, n = 15), based on the presence of flatfoot. Segmental foot kinematics were evaluated using a three‐dimensional multi‐segment foot model, and gait data of the temporal and spatial parameters were obtained. The dynamic plantar pressure was simultaneously measured using a pedobarography platform with gait trials. The protocol was repeated with all participants wearing 20 kg backpacks. Comparisons between the baseline and loaded states, as well as comparison between groups, were conducted. Results Although the cadence, gait speed, and stride length decreased in the loaded condition, step time and proportion of the stance phase increased in both groups. Although the MLA group showed more supinated and abducted positions of the forefoot and more pronated positions of the hindfoot than the CON group, the change in intersegmental foot and ankle motion in each group after backpack loading was minimal. However, the former showed a larger step width and a greater increase in contact area in the midfoot region, while the latter demonstrated a greater increase in peak pressure. Conclusions Individuals with mild flatfoot demonstrated significantly different gait curve patterns (waveforms) compared to the controls. In the loaded condition, the CON and MLA groups may have adopted different strategies to maintain balance during gait. We suggest that although individuals with asymptomatic mild flatfoot are drafted as active‐duty soldiers, they should be thoroughly investigated under loaded conditions, and orthoses may be helpful.